2020
DOI: 10.1038/s41598-020-70224-6
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative impact of cover crops on soil carbon sequestration and profitability in a temperate humid climate

Abstract: planting and termination, CC species, and cropping system, duration of the experiment), quantity and quality of CC residues, and the climatic conditions 15. Therefore, assessment of SOC storage in response to CC treatments is needed for various production systems. Cover crop research has evaluated CC effects on soil quality 13-14,16-17 and crop production 16,18-22. Long-term studies are needed to assess the potential of CCs to sequester C 4,23-25 and have primarily focused on evaluating the amount of soil C se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…The proportion of LF in the total OC was high, ranging from 14.88-26.23% in the autumn, to 13.62-23.33% in the spring, in the fertilization treatments. Our results showed that higher crop yields build up a greater supply of labile organic substrate, which in general creates a greater possibility for carbon sequestration in the soil [44].…”
Section: Very Low Soilmentioning
confidence: 68%
“…The proportion of LF in the total OC was high, ranging from 14.88-26.23% in the autumn, to 13.62-23.33% in the spring, in the fertilization treatments. Our results showed that higher crop yields build up a greater supply of labile organic substrate, which in general creates a greater possibility for carbon sequestration in the soil [44].…”
Section: Very Low Soilmentioning
confidence: 68%
“…In this context, the results reveal the importance of diversification of soil cover rotation with cover crops in intense crop cultivation systems to maintain soil C stocks (Chahal et al, 2020; Rosolem et al, 2016). The chemical composition of different cover crops with an appropriate N:lignin ratio is fundamental for C sequestration in the soil under systems using cover crop rotations in the Cerrado region.…”
Section: Resultsmentioning
confidence: 98%
“…Inclusion of legumes in crop rotations provides N to microorganisms that synthesize stable fractions of soil organic matter (SOM), in addition to promoting protection and stability of C, consequently reducing greenhouse gas (GHG) emissions (Nishigaki et al, 2021; Yao et al, 2019). The adoption of cover crops in cropping systems is recommended as a management strategy to increase soil C stocks (Chahal et al, 2020; Rosolem et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This study, however, also found wide variability and was based on those farmers who used cover crops, which may not be representative of other farmers. Another U.S. study found that cover crops were profitable for growing vegetables but not for use with grains and oilseeds (Chahal et al 2020). Because of differing conditions, these studies only suggest that the potential for cover crops to be more costeffective if continued for several years should be studied in Denmark.…”
Section: -30%mentioning
confidence: 99%